Translational Animal Models Provide Insight Into Mesenchymal Stromal Cell (MSC) Secretome Therapy - Harman, Rebecca M.; Marx, Charlotte; Van de Walle, Gerlinde R. (Frontiers in Cell and Developmental Biology, 2021)
The therapeutic potential of the mesenchymal stromal cell (MSC) secretome, consisting of all molecules secreted by MSCs, is intensively studied. MSCs can be readily isolated, expanded, and manipulated in culture, and few people argue with the ethics of their collection. Despite promising pre-clinical studies, most MSC secretome-based therapies have not been implemented in human medicine, in part because the complexity of bioactive factors secreted by MSCs is not completely understood. In addition, the MSC secretome is variable, influenced by individual donor, tissue source of origin, culture conditions, and passage. An increased understanding of the factors that make up the secretome and the ability to manipulate MSCs to consistently secrete factors of biologic importance will improve MSC therapy. To aid in this goal, we can draw from the wealth of information available on secreted factors from MSC isolated from veterinary species. These translational animal models will inspire efforts to move human MSC secretome therapy from bench to bedside.